New successes with organic pesticides 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
In Nicaragua, locally manufactured neem insecticides are helping farmers to boost the export of their organically grown crops. The neem was first planted in Nicaragua about 20 years ago in a programme to help reforest the dry regions. In 1992, a...